Are Students Ready for Their Future Career in the Event and Meeting Industry? Lessons from a Comparative Study between Students and Event and Meeting Professionals. Issue 2 (2nd April 2020) - Lee, Seonjeong (Ally); Shin, Hyejo Hailey; Jeong, Miyoung
ABSTRACT: An increasing number of students show great interest in the event and meeting industry for their future career. Event and meeting professionals have to handle challenging and dynamic circumstances, which require development of various skills, knowledge, the proper personality, and the right leadership style. It is unclear how students understand these different competencies and how event and meeting professionals view these different competencies, which play important roles for students' future careers in the event and meeting industry. Based on a self-administered, online survey, this study explores the importance of skills, knowledge, personality types, and leadership styles from both event and meeting professionals and students in the hospitality and tourism management program. Results suggest how hospitality and tourism programs can provide better education for students to be successful in the event and meeting industry.